Department of Law (Democritus University of Thrace, 2022)
: Ο Ιωσήφ Άντιος, ο Αυτοκρατηρής, ο Καλύμβερ, η Παρατηρία, ο Καλυμβίου, ο Ναυρίου, ο Ιωσήφ, ο Καλύμβερ, ο Καλύμβερ, ο Ιωσήφ, ο Καλύμβερ, ο Καλύμβερ, ο Ιωσήφ, ο Καλύμβερ, ο Ιωσήφ, ο Καλύμβερ, ο Καλύμβερ, ο Ιωσήφ, ο Καλύμβερ, ο Καλύμβερ, ο Ιωσήφ, ο Καλύμβερ, ο Ιωσήφ, ο Καλύμβερ Of our sky is quarantine What a lullaby of darkness Is this night going down They said don't let me down And we'll get another round They said don't let me down And we'll get another round All our news feeds full of stories Written by the cruelest fate Grateful tears replied no worries Texting you that's not too late All of us should taste some madness Kings and queens don't get a crown They said don't let me down And we'll get another round They said don't let me down And we'll get another round Of our sky is quarantine